Linezolid Pharmacokinetics in South African Patients with Drug-Resistant Tuberculosis and a High Prevalence of HIV Coinfection - Wasserman, Sean; Denti, Paolo; Brust, James C M; Abdelwahab, Mahmoud; Hlungulu, Siphokazi; Wiesner, Lubbe; Norman, Jennifer; Sirgel, Frederick A; Warren, Robin M; Esmail, Aliasgar; Dheda, Keertan; Gandhi, Neel R; et al. (Antimicrobial agents and chemotherapy, 2019)
The World Health Organization (WHO) recently recommended that linezolid be prioritized in treatment regimens for drug-resistant tuberculosis (TB), but there are limited data on its pharmacokinetics (PK) in patients with this disease. We conducted an observational study to explore covariate effects on linezolid PK and to estimate the probability of PK/pharmacodynamic target attainment in South African patients with drug-resistant TB. Consecutive adults on linezolid-based regimens were recruited in Cape Town and underwent intensive PK sampling at steady state. Noncompartmental analysis was performed. Thirty participants were included: 15 HIV positive, 26 on the initial dose of 600 mg daily, and 4 participants on 300 mg daily after dose reduction for linezolid-related toxicity. There was a negative correlation between body weight and exposure, with 17.4% (95% confidence interval [CI], 0.1 to 31.7) decrease in area under the concentration-time curve from 0 to 24 h (AUC ) per 10-kg weight increment after adjustment for other covariates. Age was an independent predictor of trough concentration, with an estimated 43.4% (95% CI, 5.9 to 94.2) increase per 10-year increment in age. The standard 600-mg dose achieved the efficacy target of free AUC/MIC of >119 at wild-type MIC values (≤0.5 mg/liter), but the probability of target attainment dropped to 61.5% (95% CI, 40.6 to 79.8) at the critical concentration of 1 mg/liter. When dosed at 600 mg daily, trough concentrations were above the toxicity threshold of 2 mg/liter in 57.7% (95% CI, 36.9 to 76.6). This confirms the narrow therapeutic index of linezolid, and alternative dosing strategies should be explored.